Pharmacokinetics and pharmacodynamics of tucaresol, an antisickling agent, in healthy volunteers. - Rolan, P E (1995)
1. Tucaresol is an orally administered antisickling agent which increases the oxygen affinity of haemoglobin. 2. The pharmacokinetics, effects on moderate graded exercise and psychometric performance of tucaresol were examined in a double-blind, placebo-controlled, parallel groups study in 12 healthy men. 3. Three doses of tucaresol were given at 48 h intervals intended to modify 15, 25 and 32.5% of a subject's haemoglobin to a high affinity form (%MOD). 4. Mean peak %MOD was 34%. Mean Cmax values in plasma and erythrocytes were 81.4 and 1459 micrograms ml-1, respectively. 5. Heart rate, compared with baseline, increased in the tucaresol group with the greatest changes at the highest %MOD and workload. There were no differences between groups in psychometric test performance. 6. Three volunteers on active drug developed fever, rash and tender cervical lymphadenopathy with onset 7-10 days from the start of dosing, suggesting an immune mechanism. 7. The acute increase in oxygen affinity with tucaresol is physiologically well-tolerated, but the utility of tucaresol in the management of sickle cell disease will depend on the identification of a dosing regimen with a lower incidence of drug allergy.